Evaluation the Biosorption Capacity of Water Hyacinth (Eichhornia crassipes) Root for Some Heavy Metals - M. Najem, Ali (Iraqi Journal of Science, 2023)
Heavy metals especially lead (Pb), cadmium (Cd), chromium (Cr) and copper (Cu) are noxious pollutants with immense health hazards on living organisms, these pollutants enter aquatic environment in Iraq mainly Tigris and Euphrates rivers via waste water came from different anthropological activities, This study investigated capacity of dried and ground root of water hyacinth (Eichhornia crassipes) in removing the heavy metals from their aqueous solutions. Effects of initial concentrations of the heavy metals and pH of their aqueous solutions were studied. Results of this study revealed excellent biosorption capacity of water hyacinth root in general, removal of Pb was the highest and Cr was lowest. The results showed that the Pb, Cu and Cr removal increased as their initial concentrations increased, with maximum removal of Pb and Cu was in 1000 ppm 99.66% and 96.63% respectively and 85% was the maximum removal of Cr in 750 ppm, in contrast Cd maximum removal was in 250 ppm and the adsorption decreased as initial concentrations increased. Removal of Pb, Cu and Cr was maximum with pH 4 and 5, while Cd removal was maximum with pH 8. This study paves the way to use water hyacinth in many applications to remove the heavy metals especially in waste water treatment plants.